Hierarchical colloidosomes self-assembled from block copolymer micelles via emulsion interfacial confinement. (3rd November 2021) - Liu, Changxu; Wu, Ming; Duan, Lijie; Yan, Nan; Jiang, Wei
Abstract: Hierarchical self-assembly of polymeric building blocks into high-level colloidosomes is desirable to not only design novel nanostructures but also fabricate the complex artificial materials across many length scales with multifunctionality. Although great progress has been made in the designing the hierarchical colloidosomes, the fabrication of polymeric colloidosomes self-assembled from block copolymer (BCP) colloidal nanoparticles still remains challenge. Here, we report the fabrication of the hierarchical polymeric colloidosomes with typical hollow internal structures self-assembled from the polystyrene- block -poly (2-vinyl pyridine) (PS- b -P2VP) BCP spherical micelles through the emulsion interfacial confinement, which is constructed through the water-in-1-butanol emulsion system. Moreover, the hierarchical colloidosomes can disassemble into the original uniform spherical micelles under the acid aqueous solution, indicating that the colloidosomes possess good pH stimuli-responsibility. Finally, the stability of the colloidosomes can be greatly improved by cross-linking the P2VP corona of original spherical micelles, offering the effective templates for construction of the multifunctional materials. This finding provides a simple yet effective method for the fabrication of the hierarchical colloidosomes from the BCP building blocks.